2022
DOI: 10.3389/fnut.2022.799809
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Profiles of Sauvignon Blanc Wine Following Protein Stabilization Using a Combined Ultrafiltration/Heat/Protease Treatment

Abstract: Ultrafiltration (UF) was evaluated as a process by which proteins can be selectively removed from white wine as an alternative approach to protein stabilization than traditional bentonite fining. Unfined Sauvignon Blanc wine (50 L) was fractionated by UF and the retentate stabilized either by heat and/or protease treatment or bentonite fining before being recombined with the permeate. The heat stability of recombined wine was significantly improved when retentate was heated following protease (Aspergillopepsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
3
6
0
Order By: Relevance
“…The bentonite and protease combined with heat treatments significantly reduced the total protein content in liqueur wines, with heating only, bentonite and protease combined with heat treatments reducing the protein content by 10.15%, 17.18% and 16.08%, respectively ( p < 0.05). This indicated that protease combined with heat treatment had less effect of composition in liqueur wines, in agreement with previous research that found this innovative approach to protein stabilization had no significant impact on wine quality [ 14 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The bentonite and protease combined with heat treatments significantly reduced the total protein content in liqueur wines, with heating only, bentonite and protease combined with heat treatments reducing the protein content by 10.15%, 17.18% and 16.08%, respectively ( p < 0.05). This indicated that protease combined with heat treatment had less effect of composition in liqueur wines, in agreement with previous research that found this innovative approach to protein stabilization had no significant impact on wine quality [ 14 ].…”
Section: Resultssupporting
confidence: 91%
“…The bentonite and protease combined with heat treatments significantly reduced the total protein content in liqueur wines, with heating only, bentonite and protease combined with heat treatments reducing the protein content by 10.15%, 17.18% and 16.08%, respectively (p < 0.05). This indicated that protease combined with heat treatment had less effect of composition in liqueur wines, in agreement with previous research that found this innovative approach to protein stabilization had no significant impact on wine quality [14]. The chemical class, content and sensory characteristics of volatile aroma compounds influenced the complexity of liqueur flavors, and the interaction of clarification stabilization treatments on volatile compounds depended on the properties of the compounds, the physicochemical properties of the clarifying agent and possible interactions with other macromolecules in liqueur wines [15,16].…”
Section: Chemical Components Of Liqueur Winessupporting
confidence: 92%
“…Innovative methods for haze prevention are still in demand. Recently, the use of an enzymatic mixture known as Proctase combined with flash pasteurization was approved by the International Organization of Vine and Wine (OIV) for market applications [ 67 ]. Furthermore, the combination of rTLP and rCHI and the identification of cleavage sites by MS-based peptidomics and de novo sequencing is an innovative tool to screen peptidase candidates for their ability to cleave thermolabile grape berry proteins at low pH and temperatures suitable for winemaking, providing more insights into the effects of peptidases in wine haze reduction.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, recent developments in filtration technologies have been introduced to help winemakers to reduce the problems of precipitation of unstable proteins present in white wines after bottling. This problem can cause cloudiness, which is generally considered commercially unacceptable [19].…”
Section: Innovations In Grape and Wine Productionmentioning
confidence: 99%